Polyolefin foam beads and method for producing same

JP7630623B2Active Publication Date: 2025-02-17DOW GLOBAL TECHNOLOGIES LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023534734
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-14
Publication Date
2025-02-17
Estimated Expiration
2040-12-14

Smart Images

  • Figure 0007630623000006
    Figure 0007630623000006
  • Figure 0007630623000007
    Figure 0007630623000007
  • Figure 0007630623000001
    Figure 0007630623000001
Patent Text Reader

Abstract

The present disclosure relates to polyolefin foam beads comprising one or more polyolefin interpolymers, the foam beads having a gel content of 80% or more and a tan delta at 1 rad / s of 0.11 or less, and methods for making the same. The disclosure further relates to elements prepared from the foam beads, products containing the elements, and the use of the foam beads in bead filling applications.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to polyolefin foam beads and methods of making the same. The present disclosure further relates to components prepared from the foam beads, products containing the components, and the use of the foam beads in bead filling applications. [Background technology]

[0002] Polyolefin products, such as ENGAGE™ Polyolefin Elastomers (POE) and INFUSE™ Olefin Block Copolymers (OBC), are widely used in industry. For example, in the footwear industry, components such as insoles are traditionally manufactured using crosslinked EVA / POE and EVA / OBC foams produced by chemical foaming. Such processes, however, are very labor intensive, so alternative foaming technologies with environmental and cost-saving processes are being pursued.

[0003] Bead foaming technology, a type of physical foaming, offers an option. The advantages of bead foaming compared to chemical foaming include the absence of unpleasant odors, less contamination of the mold, visual and tactile differences, and isotropic properties of the parts. Most importantly, the bead foaming process decouples the foaming process from the molding process.

[0004] Typically, there are two types of commercial uses of bead foam in the footwear industry, represented by Adidas Boost (TPU) and Nike Joyride, respectively. The former involves bead making and steam chest molding, while the latter involves bead making and filling separate beads into holes to form elements (e.g., midsoles). To ensure good sintering during steam chest molding, the foam beads should not be crosslinked or may only be partially crosslinked with a relatively low concentration of gel content. For bead-filled applications (not only in footwear but also in other applications such as saddles, pillows, etc.), the foam beads can be crosslinked and thus have relatively good elasticity.

[0005] There remains a need for foam beads having improved properties such as resiliency. Summary of the Invention

[0006] In one aspect, the present disclosure provides foam beads formed from a composition comprising one or more polyolefin interpolymers, the foam beads having a gel content of 80% or greater and a tan δ at 1 rad / s of 0.11 or less.

[0007] In a further aspect, the present disclosure provides a method for producing polyolefin foam beads, comprising: (a) providing a composition comprising one or more polyolefin interpolymers; (b) spheronizing the composition to form pellets; (c) crosslinking the pellets to a gel content of 80% or more; (d) expanding the crosslinked pellets into foam beads; The method includes providing a foam bead having a tan δ of 0.11 or less at 1 rad / s.

[0008] In a further aspect, the present disclosure provides an element prepared from a plurality of the foam beads described herein, the element comprising pores filled with the foam beads.

[0009] In a further aspect, the present disclosure provides products comprising the elements described herein.

[0010] In a further aspect, the present disclosure provides for the use of the foam beads described herein in bead-filling applications.

[0011] It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention, as claimed. [Brief description of the drawings]

[0012] [Figure 1] 1 is a graph showing Tan δ of various foam beads during a frequency sweep. [Diagram 2] 1 is a scanning electron microscope (SEM) micrograph of foam beads prepared in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and all publications, patent applications, patents, and other references mentioned herein are incorporated by reference.

[0014] The following detailed description refers to the accompanying drawings, which show, by way of example, specific details and embodiments in which the invention may be practiced. Other embodiments may be utilized, and changes may be made, without departing from the scope of the invention. The various embodiments are not necessarily mutually exclusive, as some embodiments may be combined with one or more other embodiments to form new embodiments.

[0015] In the context of the various embodiments, the articles "a," "an," and "the" used in reference to features or elements include a reference to one or more of the feature or element. All ranges include their endpoints unless otherwise indicated.

[0016] As disclosed herein, the terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any subsequent recitation any other component, step, or procedure, excepting those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically described or listed.

[0017] As disclosed herein, all percentages referred to herein are by weight and temperatures are in degrees Celsius unless otherwise specified.

[0018] A. Polyolefin foam beads The present disclosure provides polyolefin interpolymer foam beads. The foam beads are formed from a composition comprising one or more polyolefin interpolymers.

[0019] In some embodiments, foam beads may be formed from a composition including one or more polyolefin interpolymers and, optionally, one or more additives.

[0020] In some particular embodiments, the foam beads may be formed from a composition including one or more polyolefin interpolymers, where 70% or more by weight of the one or more polyolefin interpolymers are silane-grafted.

[0021] In some particular embodiments, foam beads may be formed from a composition comprising: (A) one or more polyolefin interpolymers; and (B) one or more optional additives, wherein 70% or more by weight of the one or more polyolefin interpolymers are silane-grafted.

[0022] i. Polyolefin Interpolymer As used herein, the term "polyolefin" or "olefin-based polymer" refers to a polymer that, in polymerized form, contains about 50 weight percent or majority weight percent (based on the weight of the polymer) of an olefin, such as ethylene or propylene, and may optionally contain one or more comonomers.

[0023] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, contains at least about 50 weight percent or majority weight percent ethylene (based on the weight of the polymer) and may optionally contain one or more comonomers.

[0024] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. Thus, the generic term polymer includes the term homopolymer (used to refer to a polymer prepared from only one type of monomer, with the understanding that trace amounts of impurities may be incorporated into the polymer structure), and the term interpolymer, as defined herein below. Trace amounts of impurities, such as catalyst residues, may be incorporated into and / or within the polymer. Typically, polymers are stabilized with very small amounts ("ppm" amounts) of one or more stabilizers.

[0025] As used herein, the term "interpolymer" refers to a polymer prepared by the polymerization of at least two different types of monomers. Thus, the term interpolymer includes the term copolymer (used to refer to a polymer prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.

[0026] In some embodiments, the composition may comprise 80% or more, 85% or more, 90% or more, 95% or more, 98% or more, 99% or more, or 100% by weight of polyolefin interpolymer, based on the total weight of the composition, or even based on the total weight of the foam beads. In some embodiments, the composition may comprise 80%, or 85%, or 90%, up to 95%, or 98%, or 99%, or up to 100% by weight of polyolefin interpolymer, based on the total weight of the composition, or even based on the total weight of the foam beads.

[0027] In one embodiment, the polyolefin interpolymer may have a melt index (MI) of 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less. In one embodiment, the polyolefin interpolymer may have a MI within a numerical range obtained by combining any two of the following endpoints: 0.1 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1.0 g / 10 min, 1.5 g / 10 min, 2.0 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, and 30 g / 10 min. In one embodiment, the polyolefin interpolymers can have a MI of 0.1 g / 10 min, or 0.5 g / 10 min, or 0.8 g / 10 min, or up to 1.0 g / 10 min, or 1.5 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 20 g / 10 min, or up to 30 g / 10 min. In one embodiment, the polyolefin interpolymers can have a MI of 0.1 g / 10 min to 30 g / 10 min, or 0.1 g / 10 min to 20 g / 10 min, or 0.1 g / 10 min to 10 g / 10 min, or 0.5 g / 10 min to 8 g / 10 min, or 1 g / 10 min to 5 g / 10 min.

[0028] In one embodiment, the polyolefin interpolymer has a viscosity of 0.850 g / cm 3 More than 0.855g / cm 3 More than 0.860g / cm 3 More than 0.865g / cm 3 or more than 0.870g / cm 3 In one embodiment, the polyolefin interpolymer may have a density of 0.850 g / cm or greater. 3 , 0.855g / cm 3 , 0.860g / cm 3 , 0.865g / cm 3 , 0.870g / cm 3 , 0.875g / cm 3 , 0.880g / cm 3 , 0.885g / cm 3 , 0.890g / cm 3 , 0.895g / cm 3 , 0.900g / cm 3, 0.905g / cm 3 , and 0.910 g / cm 3 In one embodiment, the polyolefin interpolymer may have a density within the range obtained by combining any two of the above. 3 , or 0.855 g / cm 3 , or 0.860 g / cm 3 , or 0.865 g / cm 3 , or 0.870 g / cm 3 , or 0.875 g / cm 3 , ~0.880g / cm 3 , or 0.885 g / cm 3 , or 0.890 g / cm 3 , or 0.895 g / cm 3 , or 0.900 g / cm 3 , or 0.905 g / cm 3 , or 0.910 g / cm 3 In one embodiment, the polyolefin interpolymer may have a density of up to 0.850 g / cm 3 ~0.910g / cm 3 , 0.855g / cm 3 ~0.910g / cm 3 , 0.860g / cm 3 ~0.910g / cm 3 , 0.865g / cm 3 ~0.905 cm 3 , or 0.870 cm 3 ~0.905cm 3 The density of the sintered body may be 0.01 to 0.01.

[0029] In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30 or greater, 35 or greater, 40 or greater, 45 or greater, or 50 or greater. In one embodiment, the polyolefin interpolymers may have a Shore A hardness within a numerical range obtained by combining any two of the following endpoints: 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, and 90. In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30, or 35, or 40, or 45, or 50, or 55, or 60, or 65, or 70, or 75, to 80, or 85, or 90. In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30-90, 35-90, 40-90, 45-90, 50-90, or 55-90.

[0030] In some embodiments, the polyolefin interpolymer may be a polyolefin elastomer (POE). In some embodiments, the polyolefin interpolymer may be selected from the group consisting of one or more ethylene / α-olefin multiblock interpolymers, one or more ethylene / α-olefin random copolymers, and any combination thereof.

[0031] (1) Ethylene / α-olefin multiblock interpolymer In some embodiments, the polyolefin interpolymer can comprise an ethylene / α-olefin multiblock interpolymer. In some embodiments, the polyolefin interpolymer can comprise an ethylene / α-olefin multiblock copolymer, such as ethylene and one or more copolymerizable C3-C 20 Ethylene / C3-C with α-olefin comonomer (and optional additives) 20The α-olefin may include an α-olefin multiblock copolymer. Non-limiting examples of suitable α-olefins include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecylene, and 1-tetradecene. In some exemplary embodiments, the α-olefin is a C3-C 10 The polyolefin interpolymer may be an α-olefin, such as a C4-C8 α-olefin. In one exemplary embodiment, the polyolefin interpolymer may comprise an ethylene / octene multiblock copolymer. In one exemplary embodiment, the ethylene / octene multiblock copolymer is sold under the trade name INFUSE™, available from The Dow Chemical Company, Midland, Michigan, USA.

[0032] As used herein, "ethylene / alpha-olefin multi-block interpolymer" or "olefin block copolymer (OBC)" refers to an interpolymer comprising ethylene and one or more copolymerizable alpha-olefin comonomers in polymerized form, characterized by a plurality of blocks or segments of two or more (preferably three or more) polymerized monomer units, the blocks or segments having different chemical or physical properties. Specifically, the term refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments (referred to as "blocks") linked in a substantially linear fashion, i.e., a polymer comprising chemically distinct units that are linked (covalently bonded) end-to-end with respect to polymerized functional groups, rather than in a pendant or grafted fashion. The blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene vs. polypropylene), size of crystals resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching including long chain branching or hyperbranching, uniformity, and / or any other chemical or physical property. Block copolymers are characterized by unique distributions of both polymer polydispersity (PDI or Mw / Mn) and block length distributions, based, for example, on the effect of the use of shuttling agents in combination with the catalyst system. Non-limiting examples of the olefin block copolymers of the present disclosure, and processes for preparing the same, are disclosed in U.S. Pat. Nos. 7,858,706 (B2), 8,198,374 (B2), 8,318,864 (B2), 8,609,779 (B2), 8,710,143 (B2), 8,785,551 (B2), and 9,243,090 (B2), all of which are incorporated herein by reference in their entireties.

[0033] Illustratively, the multi-block copolymer has the following formula: (AB) nwhere n is at least 1 and preferably an integer greater than 1, for example, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 60, 70, 80, 90, 100 or more. Here, "A" represents a hard block or segment, and "B" represents a soft block or segment. Preferably, the A and B segments are linked in a substantially linear fashion, as opposed to a substantially branched or substantially star-shaped fashion. In other embodiments, the A and B segments are randomly distributed along the polymer chain. In other words, for example, a block copolymer does not usually have the following structure: AAA-AA-BBB-BB. In still other embodiments, a block copolymer does not usually have a third type of block or segment that includes a different comonomer(s). In still yet other embodiments, each of the blocks A and B has a monomer or comonomer that is substantially randomly distributed within the block. In other words, neither block A nor block B includes two or more sub-segments (or sub-blocks) of distinct composition, such as a tip segment having a substantially different composition than the remainder of the block.

[0034] Olefin block copolymers are generally produced via a chain shuttling process, such as that described in U.S. Pat. No. 7,858,706, which is incorporated herein by reference. Some chain shuttling agents and related information are listed in column 16, line 39 to column 19, line 44. Some catalysts are listed in column 19, line 45 to column 46, line 19, and some cocatalysts are listed in column 46, line 20 to column 51, line 28. Some process features are listed in column 51, line 29 to column 54, line 56. See also: U.S. Pat. Nos. 7,608,668, 7,893,166, and 7,947,793, and U.S. Patent Publication No. 2010 / 0197880. See also U.S. Pat. No. 9,243,173.

[0035] Preferably, ethylene constitutes the majority mole fraction of the entire ethylene / α-olefin multi-block copolymer, i.e., ethylene constitutes at least 50% by weight of the entire ethylene / α-olefin multi-block copolymer. More preferably, ethylene constitutes at least 60% by weight, at least 70% by weight, or at least 80% by weight, with the remaining portion of the entire ethylene / α-olefin multi-block interpolymer comprising substantially the entire C4-C8 α-olefin comonomer. Preferably, the C4-C8 α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene. In one embodiment, the ethylene / α-olefin multi-block interpolymer contains 50% by weight, 60% by weight, or 65% by weight to 80% by weight, or 85% by weight, or 90% by weight of ethylene. For many ethylene / octene multi-block interpolymers, the composition comprises an ethylene content of greater than 80% by weight of the total ethylene / octene multi-block interpolymer and an octene content of 10% to 15% by weight, or 15% to 20% by weight of the total ethylene / octene multi-block interpolymer.

[0036] Ethylene / α-olefin multiblock copolymers contain various amounts of "hard" and "soft" segments. "Hard" segments are blocks of polymerized units in which ethylene is present in an amount of more than 90% by weight, or more than 95% by weight, or more than 95% by weight, or more than 98% by weight, up to 100% by weight, based on the weight of the polymer. In other words, the comonomer content (content of monomers other than ethylene) in the hard segments can be less than 10% by weight, or less than 5% by weight, or less than 5% by weight, or less than 2% by weight, based on the weight of the polymer, and as low as zero. In some embodiments, the hard segments contain all or substantially all units derived from ethylene. "Soft" segments are blocks of polymerized units in which the comonomer content (content of monomers other than ethylene) is more than 5% by weight, or more than 8% by weight, or more than 10% by weight, or more than 15% by weight, based on the weight of the polymer. In one embodiment, the comonomer content of the soft segments can be greater than 20% by weight, or greater than 25% by weight, or greater than 30% by weight, or greater than 35% by weight, or greater than 40% by weight, or greater than 45% by weight, or greater than 50% by weight, or greater than 60% by weight, up to 100% by weight.

[0037] The soft segment may be present in the ethylene / α-olefin multiblock interpolymer at 1% by weight, or 5% by weight, or 10% by weight, or 15% by weight, or 20% by weight, or 25% by weight, or 30% by weight, or 35% by weight, or 40% by weight, or 45% by weight to 55% by weight, or 60% by weight, or 65% by weight, or 70% by weight, or 75% by weight, or 80% by weight, or 85% by weight, or 90% by weight, or 95% by weight, or 99% by weight of the total weight of the ethylene / α-olefin multiblock interpolymer. Conversely, the hard segment may be present in a similar range. The soft segment weight percentage and the hard segment weight percentage may be calculated based on data obtained from DSC or NMR. Such methods and calculations are disclosed, for example, in U.S. Pat. No. 7,608,668, the disclosure of which is incorporated herein by reference in its entirety. Specifically, the weight percent of the hard and soft segments and the comonomer content may be determined as described in US Pat. No. 7,608,668, columns 57-63.

[0038] In embodiments, the ethylene / α-olefin multi-block copolymers are produced in a continuous process and have a polydispersity index (Mw / Mn) of 1.7 to 3.5, or 1.8 to 3, or 1.8 to 2.5, or 1.8 to 2.2. When produced in a batch or semi-batch process, the ethylene / α-olefin multi-block copolymers have a Mw / Mn of 1.0 to 3.5, or 1.3 to 3, or 1.4 to 2.5, or 1.4 to 2.

[0039] A suitable ethylene / α-olefin multi-block interpolymer may be INFUSE™ from Dow, such as INFUSE™ D9130.05.

[0040] (2) Ethylene / α-olefin random copolymer In some embodiments, the polyolefin interpolymer may comprise an ethylene / α-olefin random interpolymer. The ethylene / α-olefin random copolymer may be an ethylene / propylene random copolymer or an ethylene / C4-C8 α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer may be an ethylene / C4-C8 α-olefin copolymer. The ethylene / C4-C8 α-olefin copolymer is composed of or otherwise consists of ethylene and one polymerized form of a copolymerizable C4-C8 α-olefin comonomer. The C4-C8 α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene.

[0041] Suitable ethylene / α-olefin random copolymers may be ENGAGE™ manufactured by Dow, such as ENGAGE™ 8150, or ENGAGE™ 7467.

[0042] ii. Silane-grafted polyolefin interpolymer At least a portion of the polyolefin interpolymer included in the composition for forming the foam beads as described may be silane-grafted. In other words, the composition may include a silane-grafted polyolefin interpolymer formed using a polyolefin interpolymer as described grafted with a silane monomer. In some exemplary embodiments, the silane-grafted polyolefin interpolymer is a silane-grafted ethylene / C3-C 20 α-Olefin multiblock copolymers, e.g., silane-grafted ethylene / C3-C 10 It can be an α-olefin multiblock copolymer. In another exemplary embodiment, the silane-grafted polyolefin interpolymer can be a silane-grafted ethylene / α-olefin random copolymer, for example, a silane-grafted ethylene / C4-C8 α-olefin random copolymer.

[0043] The "silane monomer" used to functionalize the polyolefin interpolymer is a silane-containing monomer that can be grafted to the polyolefin interpolymer to form a silane-functionalized polyolefin interpolymer and crosslink the polyolefin interpolymer. In some embodiments, the silane monomer can be a hydrolyzable silane monomer. Non-limiting examples of suitable hydrolyzable silane monomers include vinyltrimethoxysilane (VTMS), vinyltriethoxysilane (VTES), vinyltriacetoxysilane, and gamma-(meth)acryloxypropyltrimethoxysilane. In an exemplary embodiment, the hydrolyzable silane monomer can be VTMS.

[0044] The silane-grafted polyolefin interpolymer may be formed by a process such as the Sioplas process, in which a hydrolyzable silane monomer (such as a vinyl silane monomer) is grafted onto the backbone of the polyolefin interpolymer. The hydrolyzable silane monomer may be grafted to the polyolefin interpolymer using a suitable amount of an organic peroxide, such as 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane, to form the silane-grafted polyolefin interpolymer.

[0045] In some embodiments, the silane-grafted polyolefin interpolymer may comprise a silane grafting rate of more than 0.3 wt%, more than 0.5 wt%, more than 0.6 wt%, more than 0.8 wt%, or more than 1.0 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. In some embodiments, the silane-grafted polyolefin interpolymer may comprise a silane grafting rate of 0.1 wt%, or 0.3 wt%, or 0.5 wt%, or 0.6 wt%, or 0.8 wt%, or 1.0 wt%, to 1.1 wt%, or 1.2 wt%, or 1.5 wt%, or 1.8 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. In some embodiments, the silane-grafted polyolefin interpolymer may comprise a silane grafting ratio of 0.1 wt% to 5.0 wt%, 0.3 wt% to 4.0 wt%, or 0.5 wt% to 3.0 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. As used herein, the term "silane grafting ratio" refers to the ratio of the weight of silane grafted onto the silane-grafted polyolefin interpolymer to the total weight of the silane-grafted polyolefin interpolymer.

[0046] In some embodiments, the foam beads may be formed from a composition comprising 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, 95% by weight or more, 98% by weight or more, 99% by weight or more, or 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) included in the composition. In some embodiments, the foam beads may be formed from a composition comprising 70% by weight, or 75% by weight, or 80% by weight, or 85% by weight, to 90% by weight, or 95% by weight, or 98% by weight, or 99% by weight, or up to 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) included in the composition. In some embodiments, the foam beads may be formed from a composition comprising 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) included in the composition.

[0047] The silane-grafted polyolefin interpolymers are useful for crosslinking via silane chemistry, it being understood that crosslinking can be accomplished by other methods than silane chemistry, such as e-beam irradiation, gamma irradiation, or crosslinking based on free radical chemistry.

[0048] iii. Non-silane grafted polyolefin interpolymers The composition for forming foam beads comprising the above-mentioned silane-grafted polyolefin interpolymer may comprise a non-silane-grafted polyolefin interpolymer. As used herein, "non-silane-grafted polyolefin interpolymer" refers to one or more polyolefin interpolymers that are included in the composition for forming foam beads in addition to the above-mentioned silane-grafted polyolefin interpolymer.

[0049] The non-silane grafted polyolefin interpolymer may include any polyolefin interpolymer described herein that is not grafted with a silane. The non-silane grafted polyolefin interpolymer differs from the silane grafted polyolefin interpolymer described above at least because the non-silane grafted polyolefin interpolymer is not silane functionalized or silane grafted.

[0050] In embodiments, the non-silane-grafted polyolefin interpolymer and the polyolefin interpolymer used to form the silane-grafted polyolefin interpolymer may be physically and / or compositionally and / or structurally the same or different.

[0051] In some embodiments, the foam beads may be formed from a composition comprising 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 5% or less, 3% or less, 2% or less, or 1% or less, or 0% by weight of non-silane grafted polyolefin interpolymer based on the total weight of polyolefin interpolymer(s) included in the composition. In some embodiments, the foam beads may be formed from a composition comprising 0% or 1% or 2% or 3% or 5% to 10% or 15% or 20% or 25% or up to 30% by weight of non-silane grafted polyolefin interpolymer based on the total weight of polyolefin interpolymer(s) included in the composition. In some embodiments, the foam beads may be formed from a composition that does not include non-silane grafted polyolefin interpolymer.

[0052] In some embodiments, the non-silane grafted polyolefin interpolymer may be a non-modified polyolefin interpolymer. Examples of suitable non-modified polyolefin interpolymers include ethylene or propylene random / block copolymers such as INFUSE™, ENGAGE™, VERSIFY™, and the like.

[0053] In some embodiments, the composition for forming the foam beads may further comprise a polyolefin derivative, such as an ethylene vinyl acetate (EVA) copolymer with a high VA content (e.g., having a VA content of more than 18% by weight based on the total weight of the EVA). Suitable examples of EVA copolymers include ELVAX® 460, ELVAX® 360, ELVAX® 265, ELVAX® 260, ELVAX® 250, ELVAX® 40L-03.

[0054] iv. Additives The composition may include one or more optional additives. Non-limiting examples of suitable additives include nucleating agents, cell size stabilizers, antioxidants, colorants, inorganic fillers, flow aids, viscosity control agents, and combinations thereof.

[0055] In one embodiment, the foam beads are formed from a composition that includes 0 wt%, or 0.01 wt% to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt% of one or more optional additives, based on the total weight of the composition, or further based on the total weight of the foam beads. In another embodiment, the foam beads are formed from a composition that contains 0 wt% to 5 wt%, or 0 wt% to 1 wt%, or 0.01 wt% to 5 wt% of optional additives, based on the total weight of the composition, or further based on the total weight of the foam beads.

[0056] v. Foam beads The foam beads of the present application may be formed from a composition comprising one or more polyolefin interpolymers and, optionally, one or more additives. In some embodiments, the foam beads may be formed from a composition comprising 80 wt%, or 85 wt%, or 90 wt%, to 95 wt%, or 98 wt%, or 99 wt%, or up to 100 wt%, of the polyolefin interpolymer described herein, based on the total weight of the composition, or further based on the total weight of the foam bead, and 0 wt%, or 0.01 wt% to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt%, of one or more optional additives, based on the total weight of the composition, or further based on the total weight of the foam bead.

[0057] In some particular embodiments, the foam beads of the present application may be formed from a composition comprising one or more polyolefin interpolymers, wherein 70% or more by weight of the one or more polyolefin interpolymers are silane-grafted.

[0058] In some embodiments, the compositions may optionally include one or more optional additives.

[0059] In some embodiments, the foam beads include (A) 80% by weight, or 85% by weight, or 90% by weight, to 95% by weight, or 98% by weight, or 99% by weight, or up to 100% by weight, of one or more polyolefin interpolymers, based on the total weight of the composition, or further based on the total weight of the foam beads; (B) optionally, 0 wt. %, or 0.01 wt. % to 0.3 wt. %, or 0.5 wt. %, or 1 wt. %, or 2 wt. %, or 3 wt. %, or 5 wt. %, of one or more optional additives, based on the total weight of the composition, or further based on the total weight of the foam beads; The one or more polyolefin interpolymers include 70 wt%, or 75 wt%, or 80 wt%, or 85 wt%, to 90 wt%, or 95 wt%, or 98 wt%, or 99 wt%, or up to 100 wt%, of one or more silane-grafted polyolefin interpolymers, based on the total weight of the polyolefin interpolymer(s) included in the composition, and 0 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt%, to 10 wt%, or 15 wt%, or 20 wt%, or 25 wt%, or up to 30 wt%, of one or more non-silane-grafted polyolefin interpolymers, based on the total weight of the polyolefin interpolymer(s) included in the composition.

[0060] In some embodiments, the foam beads may have a gel content of 80% or more, 85% or more, or 90% or more, hi some embodiments, the foam beads may have a gel content of 80%, or 85%, up to 90%, or 95%, or 98%, or 99%, or up to 100%.

[0061] In some embodiments, foam beads may be formed from pellets of the composition as described. In some embodiments, foam beads may be formed from crosslinked pellets of the composition as described. In some embodiments, the crosslinked pellets of the composition may have a gel content of 80% or more, 85% or more, or 90% or more. In some embodiments, the crosslinked pellets may have a gel content of 80%, or 85%, up to 90%, or 95%, or 98%, or 99%, or up to 100%. In some embodiments, foam beads are formed from the above compositions by crosslinking pellets of the composition prior to expanding the pellets. In some embodiments, foam beads are formed by expanding crosslinked pellets of the above compositions.

[0062] In some embodiments, the foam beads can have a foam density of less than 0.20 g / cc. In some embodiments, the foam beads have a foam density of 0.06 g / cc, or 0.07 g / cc, or 0.08 g / cc, or 0.09 g / cc, or 0.10 g / cc, or 0.11 g / cc, or 0.12 g / cc, or 0.13 g / cc, to 0.14 g / cc, or 0.15 g / cc, or 0.16 g / cc, or 0.17 g / cc, or 0.18 g / cc, or 0.19 g / cc, or 0.20 g / cc. In some embodiments, the foam beads can have a foam density of 0.06 g / cc to 0.20 g / cc, 0.08 g / cc to 0.18 g / cc, 0.10 g / cc to 0.17 g / cc, or 0.12 g / cc to 0.16 g / cc.

[0063] In some embodiments, the foam beads may have a tan δ at 0.1 rad / s of 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, or 0.12 or less. In some embodiments, the foam beads may have a tan δ at 1 rad / s of 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, or 0.10 or less. In some embodiments, the foam beads may have a tan δ at 10 rad / s of 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, or 0.08 or less.

[0064] In some embodiments, the foam beads may have an average cell size of less than about 100 μm, hi some embodiments, the foam beads may have an average cell size of about 10 μm, about 15 μm, about 20 μm, up to 80 μm, or 85 μm, or 90 μm, or 95 μm, or up to 100 μm.

[0065] In some embodiments, the foam beads can be prepared by using the methods for making polyolefin foam beads as described below.

[0066] B. Method for Producing Polyolefin Foam Beads The present disclosure provides a method for producing polyolefin foam beads, comprising: (a) providing a composition comprising one or more polyolefin interpolymers; (b) spheronizing the composition to form pellets; (c) crosslinking the pellets to a gel content of 80% or more; (d) expanding the crosslinked pellets into foam beads; The method includes providing a foam bead having a tan δ of 0.11 or less at 1 rad / s.

[0067] i. Polyolefin composition The method for producing the polyolefin foam beads described herein includes (a) providing a composition comprising one or more polyolefin interpolymers, which composition may also be referred to herein as the "composition" or "polyolefin composition."

[0068] In some embodiments, the compositions provided herein may include one or more polyolefin interpolymers (e.g., one or more of those described in the "Polyolefin Foam Beads" section above) and, optionally, one or more additives.

[0069] In some embodiments, the composition may comprise 80% or more, 85% or more, 90% or more, 95% or more, 98% or more, 99% or more, or 100% by weight of polyolefin interpolymer based on the total weight of the composition. In some embodiments, the composition may comprise 80%, or 85%, or 90%, up to 95%, or 98%, or 99%, or up to 100% by weight of polyolefin interpolymer based on the total weight of the composition.

[0070] In one embodiment, the polyolefin interpolymers may have a melt index (MI) of 30 g / 10 min or less, 20 g / 10 min or less, 10 g / 10 min or less, or 5 g / 10 min or less. In one embodiment, the polyolefin interpolymers may have a MI within a numerical range obtained by combining any two of the following endpoints: 0.1 g / 10 min, 0.5 g / 10 min, 0.8 g / 10 min, 1.0 g / 10 min, 1.5 g / 10 min, 2.0 g / 10 min, 5 g / 10 min, 10 g / 10 min, 20 g / 10 min, and 30 g / 10 min. In one embodiment, the polyolefin interpolymers can have a MI of 0.1 g / 10 min, or 0.5 g / 10 min, or 0.8 g / 10 min, or up to 1.0 g / 10 min, or 1.5 g / 10 min, or 2.0 g / 10 min, or 5 g / 10 min, or 10 g / 10 min, or 20 g / 10 min, or up to 30 g / 10 min. In one embodiment, the polyolefin interpolymers can have a MI of 0.1 g / 10 min to 30 g / 10 min, or 0.1 g / 10 min to 20 g / 10 min, or 0.1 g / 10 min to 10 g / 10 min, or 0.5 g / 10 min to 8 g / 10 min, or 1 g / 10 min to 5 g / 10 min.

[0071] In one embodiment, the polyolefin interpolymer has a viscosity of 0.850 g / cm 3 More than 0.855g / cm 3 More than 0.860g / cm 3 More than 0.865g / cm 3 or more than 0.870g / cm 3 In one embodiment, the polyolefin interpolymer may have a density of 0.850 g / cm or greater. 3 , 0.855g / cm 3 , 0.860g / cm 3 , 0.865g / cm 3 , 0.870g / cm 3 , 0.875g / cm 3 , 0.880g / cm 3 , 0.885g / cm 3 , 0.890g / cm 3 , 0.895g / cm 3 , 0.900g / cm 3 , 0.905g / cm3 , and 0.910 g / cm 3 In one embodiment, the polyolefin interpolymer may have a density within the range obtained by combining any two of the above. 3 , or 0.855 g / cm 3 , or 0.860 g / cm 3 , or 0.865 g / cm 3 , or 0.870 g / cm 3 , or 0.875 g / cm 3 , ~0.880g / cm 3 , or 0.885 g / cm 3 , or 0.890 g / cm 3 , or 0.895 g / cm 3 , or 0.900 g / cm 3 , or 0.905 g / cm 3 , or 0.910 g / cm 3 In one embodiment, the polyolefin interpolymer may have a density of up to 0.850 g / cm 3 ~0.910g / cm 3 , 0.855g / cm 3 ~0.910g / cm 3 , 0.860g / cm 3 ~0.910g / cm 3 , 0.865g / cm 3 ~0.905 cm 3 , or 0.870 cm 3 ~0.905cm 3 The density of the sintered body may be 0.01 to 0.01.

[0072] In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30 or greater, 35 or greater, 40 or greater, 45 or greater, or 50 or greater. In one embodiment, the polyolefin interpolymers may have a Shore A hardness within a numerical range obtained by combining any two of the following endpoints: 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, and 90. In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30, or 35, or 40, or 45, or 50, or 55, or 60, or 65, or 70, or 75, to 80, or 85, or 90. In one embodiment, the polyolefin interpolymers may have a Shore A hardness of 30-90, 35-90, 40-90, 45-90, 50-90, or 55-90.

[0073] In some embodiments, the polyolefin interpolymer may be a polyolefin elastomer (POE). In some embodiments, the polyolefin interpolymer may be selected from the group consisting of ethylene / α-olefin multiblock interpolymers, ethylene / α-olefin random copolymers, and combinations thereof.

[0074] In some embodiments, the polyolefin interpolymer can comprise an ethylene / α-olefin multiblock interpolymer. In some embodiments, the polyolefin interpolymer can comprise an ethylene / α-olefin multiblock copolymer, such as ethylene and one or more copolymerizable C3-C 20 Ethylene / C3-C with α-olefin comonomer (and optional additives) 20 The α-olefin may include an α-olefin multiblock copolymer. Non-limiting examples of suitable α-olefins include 1-propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecylene, and 1-tetradecene. In some exemplary embodiments, the α-olefin is a C3-C 10The polyolefin interpolymer may be an α-olefin, such as a C4-C8 α-olefin. In one exemplary embodiment, the polyolefin interpolymer may comprise an ethylene / octene multiblock copolymer. In one exemplary embodiment, the ethylene / octene multiblock copolymer is commercially available from Dow and sold under the trade name INFUSE™.

[0075] A suitable ethylene / α-olefin multi-block interpolymer may be INFUSE™ from Dow, such as INFUSE™ D9130.05.

[0076] In some embodiments, the polyolefin interpolymer may comprise an ethylene / α-olefin random interpolymer. The ethylene / α-olefin random copolymer may be an ethylene / propylene random copolymer or an ethylene / C4-C8 α-olefin random copolymer. In one embodiment, the ethylene / α-olefin copolymer may be an ethylene / C4-C8 α-olefin copolymer. The ethylene / C4-C8 α-olefin copolymer is composed of or otherwise consists of ethylene and one polymerized form of a copolymerizable C4-C8 α-olefin comonomer. The C4-C8 α-olefin comonomer may be selected from 1-butene, 1-hexene, and 1-octene.

[0077] Suitable ethylene / α-olefin random copolymers may be ENGAGE™ manufactured by Dow, such as ENGAGE™ 8150, or ENGAGE™ 7467.

[0078] In some embodiments, the compositions provided herein may optionally include one or more additives. Non-limiting examples of suitable additives include nucleating agents, cell size stabilizers, antioxidants, colorants, inorganic fillers, flow aids, viscosity control agents, and combinations thereof.

[0079] In one embodiment, the composition may comprise 0 wt%, or 0.01 wt% to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt%, of one or more optional additives, based on the total weight of the composition. In another embodiment, the composition may comprise 0 wt% to 5 wt%, or 0 wt% to 1 wt%, or 0.01 wt% to 5 wt%, of one or more optional additives, based on the total weight of the composition.

[0080] In some embodiments, the composition may comprise 80 wt%, or 85 wt%, or 90 wt%, to 95 wt%, or 98 wt%, or 99 wt%, or 100 wt%, of a polyolefin interpolymer described herein, based on the total weight of the composition, and 0 wt%, or 0.01 wt% to 0.3 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt%, of one or more optional additives, based on the total weight of the composition.

[0081] In some particular embodiments, the compositions provided herein may comprise one or more polyolefin interpolymers, wherein 70% or more by weight of the one or more polyolefin interpolymers are silane-grafted.

[0082] In some particular embodiments, the compositions provided herein may optionally include one or more optional additives.

[0083] In some embodiments, the composition may include a silane-grafted polyolefin interpolymer. The silane-grafted polyolefin interpolymer may include any polyolefin interpolymer described herein that has been further functionalized or grafted with a silane monomer.

[0084] In some exemplary embodiments, the silane-grafted polyolefin interpolymer is an ethylene / C3-C6 copolymer as described above grafted with a silane monomer. 20 α-Olefin multiblock copolymers, i.e., silane-grafted ethylene / C3-C 20α-Olefin multiblock copolymers, e.g., silane-grafted ethylene / C3-C 10 It may be an α-olefin multiblock copolymer. In another exemplary embodiment, the silane-grafted polyolefin interpolymer may be an ethylene / α-olefin random copolymer as described, grafted with a silane monomer, i.e., a silane-grafted ethylene / α-olefin random copolymer, such as a silane-grafted ethylene / C4-C8 α-olefin random copolymer. In some embodiments, the silane monomer may be a hydrolyzable silane monomer. Non-limiting examples of suitable hydrolyzable silane monomers include vinyltrimethoxysilane (VTMS), vinyltriethoxysilane (VTES), vinyltriacetoxysilane, and gamma-(meth)acryloxypropyltrimethoxysilane. In an exemplary embodiment, the hydrolyzable silane monomer may be VTMS.

[0085] The silane-grafted polyolefin interpolymer may be formed by a process such as the Sioplas process, in which a hydrolyzable silane monomer (such as a vinyl silane monomer) is grafted onto the backbone of the polyolefin interpolymer. The hydrolyzable silane monomer may be grafted to the polyolefin interpolymer by using a suitable amount of an organic peroxide, such as 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, to form the silane-grafted polyolefin interpolymer.

[0086] In some embodiments, the silane-grafted polyolefin interpolymer may comprise a silane grafting rate of more than 0.3 wt%, more than 0.5 wt%, more than 0.6 wt%, more than 0.8 wt%, or more than 1.0 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. In some embodiments, the silane-grafted polyolefin interpolymer may comprise a silane grafting rate of 0.1 wt%, or 0.3 wt%, or 0.5 wt%, or 0.6 wt%, or 0.8 wt%, or 1.0 wt%, to 1.1 wt%, or 1.2 wt%, or 1.5 wt%, or 1.8 wt%, or 2.0 wt%, or 2.5 wt%, or 3.0 wt%, or 4.0 wt%, or 5.0 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. In some embodiments, the silane-grafted polyolefin interpolymer can comprise a silane grafting rate of 0.1 wt.% to 5.0 wt.%, 0.3 wt.% to 4.0 wt.%, or 0.5 wt.% to 3.0 wt.%, based on the total weight of the silane-grafted polyolefin interpolymer.

[0087] In one embodiment, the composition may comprise 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, 98% or more, 99% or more, or 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) contained in the composition. In one embodiment, the composition may comprise 70% or 75% or 80% or 85% by weight, up to 90% or 95% by weight, or 98% by weight, or 99% by weight, or up to 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) contained in the composition. In one embodiment, the composition may comprise 100% by weight of the silane-grafted polyolefin interpolymer based on the total weight of the polyolefin interpolymer(s) contained in the composition.

[0088] In some embodiments, the composition may include a non-silane-grafted polyolefin interpolymer.

[0089] The non-silane grafted polyolefin interpolymer may include any polyolefin interpolymer described herein that is not grafted with a silane. The non-silane grafted polyolefin interpolymer differs from the silane grafted polyolefin interpolymer described above at least because the non-silane grafted polyolefin interpolymer is not silane functionalized or silane grafted.

[0090] In embodiments, the non-silane-grafted polyolefin interpolymer and the polyolefin interpolymer used to form the silane-grafted polyolefin interpolymer may be physically and / or compositionally and / or structurally the same or different.

[0091] In one embodiment, the composition may comprise 30% or less, 25% or less, 20% or less, 15% or less, 10% or less, 5% or less, 3% or less, 2% or less, or 1% or less, or 0% by weight of non-silane grafted polyolefin interpolymer based on the total weight of polyolefin interpolymer(s) contained in the composition. In one embodiment, the composition may comprise 0% or 1% or 2% or 3% or 5% to 10% or 15% or 20% or 25% or up to 30% by weight of non-silane grafted polyolefin interpolymer based on the total weight of polyolefin interpolymer(s) contained in the composition. In one embodiment, the composition may be free of non-silane grafted polyolefin interpolymer.

[0092] In some embodiments, the non-silane grafted polyolefin interpolymer may be a non-modified polyolefin interpolymer. Examples of suitable non-modified polyolefin interpolymers include ethylene or propylene random / block copolymers such as INFUSE™, ENGAGE™, VERSIFY™, and the like.

[0093] In some embodiments, the composition for forming the foam beads may further comprise a polyolefin derivative, such as an ethylene vinyl acetate (EVA) copolymer with a high VA content (e.g., having a VA content of more than 18% by weight based on the total weight of the EVA). Suitable examples of EVA copolymers include ELVAX® 460, ELVAX® 360, ELVAX® 265, ELVAX® 260, ELVAX® 250, ELVAX® 40L-03.

[0094] In some embodiments, the composition may include one or more optional additives. The one or more additives optionally included in the composition may be those described above.

[0095] In some embodiments, the composition comprises: (A) 80% by weight, or 85% by weight, or 90% by weight, to 95% by weight, or 98% by weight, or 99% by weight, or up to 100% by weight, of one or more polyolefin interpolymers, based on the total weight of the composition, or further based on the total weight of the foam beads; (B) optionally, 0 wt. %, or 0.01 wt. % to 0.3 wt. %, or 0.5 wt. %, or 1 wt. %, or 2 wt. %, or 3 wt. %, or 5 wt. %, based on the total weight of the composition, or further based on the total weight of the foam beads, of one or more optional additives; The one or more polyolefin interpolymers include 70 wt%, or 75 wt%, or 80 wt%, or 85 wt%, to 90 wt%, or 95 wt%, or 98 wt%, or 99 wt%, or up to 100 wt%, of one or more silane-grafted polyolefin interpolymers, based on the total weight of the polyolefin interpolymer(s) included in the composition, and 0 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 5 wt%, to 10 wt%, or 15 wt%, or 20 wt%, or 25 wt%, or up to 30 wt%, of one or more non-silane-grafted polyolefin interpolymers, based on the total weight of the polyolefin interpolymer(s) included in the composition.

[0096] ii. Prillization The method of making the polyolefin foam beads described herein includes (b) spheronizing the composition to form pellets.

[0097] In some embodiments, the pellets (also referred to herein as "micropellets") can be substantially spherical. In some embodiments, the pellets can have a diameter of 1.8 mm, or 2.0 mm, or 2.3 mm to 3.0 mm, or 3.5 mm, or 3.8 mm. In certain embodiments, the pellets can have a diameter of 2.3 mm to 3.0 mm.

[0098] In some embodiments, the prilling can be carried out by using a pelletizer to produce pellets of the composition. In some embodiments, the prilling can be carried out by underwater prilling. Generally, underwater prilling can be carried out by using an underwater pelletizer equipped with a die plate having a multiple hole system, generally having multiple holes.

[0099] iii. Crosslinking The method of making the polyolefin foam beads described herein includes (c) crosslinking the pellets.

[0100] In the method of the present disclosure, the crosslinking step is carried out before the foaming step.

[0101] In some embodiments, crosslinking is carried out to a gel content of about 80% or more, about 85% or more, or about 90% or more, in some embodiments, crosslinking can be carried out to a gel content of about 80%, or about 85%, to about 90%, or about 95%, or about 98%, or about 99%, or about 100%.

[0102] In some embodiments, crosslinking may be performed by methods using silane chemistry, electron beam irradiation, gamma irradiation, or free radical chemistry based crosslinking. In certain embodiments, crosslinking may be performed by using silane chemistry, i.e., silane crosslinking.

[0103] In some embodiments, a crosslinking agent may be used to crosslink the pellets of the composition. The crosslinking agent is not particularly limited as long as it can crosslink the copolymer. As the crosslinking agent, a well-known organic peroxide used for crosslinking polyethylene resins may be used. Examples thereof include percumyl compounds such as dicumyl peroxide and tert-butyl cumyl peroxide, perbutyl compounds such as 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and di-tert-butyl peroxide, perhexyl compounds such as tert-hexyl peroxybenzoate, and perocta compounds such as 1,1,3,3-tetramethylbutylperoxy-2-ethylhexanoate. These compounds may be used alone or in combination of two or more. In some exemplary embodiments, the lower limit of the amount of one or more crosslinking agents mixed can be about 0.05 parts by weight, about 0.1 parts by weight, about 0.2 parts by weight, about 0.3 parts by weight, about 0.4 parts by weight, or about 0.5 parts by weight per 100 parts by weight of the total weight of the polymer. The upper limit of the amount of one or more crosslinking agents mixed can be about 5.0 parts by weight, about 4.5 parts by weight, about 4.0 parts by weight, about 3.5 parts by weight, about 3.0 parts by weight, or about 2.5 parts by weight per 100 parts by weight of the total weight of the polymer.

[0104] In some embodiments, crosslinking can be carried out at a temperature of about 20°C, or about 40°C, or about 60°C, or about 80°C, or about 100°C, to about 120°C, or about 150°C, or about 180°C, or about 200°C, or about 220°C.

[0105] In some embodiments, crosslinking may be performed by irradiation at a dosage of, for example, 30KGy to 80KGy, 40KGy to 70KGy, or 45KGy to 60KGy.

[0106] In one exemplary embodiment where silane crosslinking is utilized, the crosslinking may be carried out by immersing pellets of the composition comprising the silane-grafted polyolefin interpolymer in a catalyst (e.g., dibutyltin dilaurate) or a silane solution thereof and exposing the pellets to air for wet crosslinking of the silane moieties.

[0107] In another exemplary embodiment where silane crosslinking is utilized, the crosslinking may be carried out by immersing pellets of the composition comprising the silane-grafted polyolefin interpolymer in hot water (e.g., at temperatures greater than 80° C.) for moisture crosslinking of the silane moieties.

[0108] iv. Foaming The method of making polyolefin foam beads described herein includes (d) expanding the crosslinked pellets into foam beads.

[0109] In the method of the present disclosure, the foaming step is carried out after the crosslinking step.

[0110] In some embodiments, the foaming can be physical foaming.

[0111] In some embodiments, an expansion agent may be used to expand the crosslinked pellets. The expansion agent used for expansion is not particularly limited as long as it can expand the crosslinked particles. Examples of the expansion agent include inorganic physical expansion agents such as air, nitrogen, carbon dioxide, argon, helium, oxygen, and neon, and organic physical expansion agents such as aliphatic hydrocarbons such as propane, n-butane, isobutane, n-pentane, isopentane, and n-hexane, alicyclic hydrocarbons such as cyclohexane and cyclopentane, halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride, and dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. Among these, inorganic physical expansion agents are preferred because they do not destroy the ozone layer and are inexpensive, and nitrogen, air, and carbon dioxide are more preferred, and carbon dioxide is particularly preferred. The expansion agents may be used alone or in combination of two or more. In some embodiments, the amount of the expansion agent used may be determined taking into consideration the apparent density of the desired expanded beads, the type of multiblock copolymer, the type of expansion agent, etc., and is generally about 2 to about 20 parts by weight for organic physical expansion agents and about 0.5 to about 20 parts by weight for inorganic physical expansion agents per 100 parts by weight of the total weight of the polymer.

[0112] In some embodiments, foaming can be carried out at a temperature near the melting temperature of the polymer, hi some embodiments, foaming can be carried out at a temperature of about 70°C, or about 80°C, or about 90°C, or about 100°C, up to about 110°C, or about 120°C, or about 130°C, or about 140°C, or up to about 150°C.

[0113] In some embodiments, foaming may be carried out at a pressure of about 10 bar, or about 20 bar, or about 30 bar, or about 40 bar, or about 50 bar, or about 60 bar, up to about 100 bar, or about 120 bar, or about 150 bar, or about 180 bar, or about 200 bar, or about 220 bar. In one exemplary embodiment, foaming may be carried out at a pressure ranging from about 50 bar to about 200 bar.

[0114] In some embodiments, the foam beads can be conditioned (eg, at room temperature) to allow gas exchange between the inside and outside of the beads.

[0115] In some embodiments, the foam beads may have an average cell size of less than about 100 μm, hi some embodiments, the foam beads may have an average cell size of about 10 μm, about 15 μm, about 20 μm, up to 80 μm, or 85 μm, or 90 μm, or 95 μm, or up to 100 μm.

[0116] Unexpectedly, it has been found that crosslinking before foaming results in improved elasticity. When crosslinking is performed before bead foaming (i.e., crosslinking of the micropellets before foaming, "pre-XL"), the energy loss (characterized by tan δ in dynamic mechanical analysis (DMA) of the resulting foam beads) can be significantly reduced compared to the post-crosslinking approach (i.e., crosslinking of the foam beads, "post-XL"). In other words, pre-XL can be one factor that can significantly enhance elasticity. This is especially true when such pre-XL bead foams have a gel content of ≧80%, especially ≧90%. Such highly crosslinked high elasticity bead foams can find promising potential use in bead-filling applications.

[0117] C. Foam Bead Filling Elements and Products The present disclosure further provides elements prepared from the foam beads described herein.

[0118] In some embodiments, the element can be a foam bead-filled element. In some embodiments, the element can include holes filled with foam beads as described. In some embodiments, the element can be prepared from foam beads as described via a bead-filling application. In some embodiments, the element can be prepared by (i) filling the holes with foam beads as described via the bead-filling port of the hole, and (ii) closing the hole, for example, by closing all of the openings of the hole, including the bead-filling port of the hole. In some embodiments, the hole can be a mold hole. In some embodiments, the hole can be a predetermined shape. In some embodiments, the hole can be made from inorganic and / or organic materials, including fabrics, polymers, leather, rubber, fibers, etc.

[0119] The present disclosure further provides an article of manufacture comprising the above elements. In some embodiments, the article of manufacture may comprise foam bead filler elements as part. Examples of articles of manufacture may include, but are not limited to, articles for use in automotive parts, footwear components (such as insoles), molded articles (such as toys or other household items), building materials, and the like.

[0120] The present disclosure further provides for the use of the foam beads described herein in bead-filling applications. EXAMPLES

[0121] Certain embodiments of the present invention are now illustrated in the following examples, in which all parts and percentages are by weight unless otherwise specified.

[0122] raw material INFUSE™ D913 0.05 olefin block copolymer (ethylene / octene multiblock copolymer), density 0.886 g / cm 3 (ASTM D792), MI 1.5g / 10min (ASTM D1238, 190℃ / 2.16kg), Shore A=80 (ASTM D2240).

[0123] Luperox 101 peroxide: 2,5-dimethyl-2,5-di-(tert-butylperoxy)hexane from Arkema.

[0124] XIAMETER OFS-6300: Vinyltrimethoxysilane (VTMS) manufactured by Dow Corning.

[0125] DBTDL: Dibutyltin dilaurate, a catalyst for silane wet curing, manufactured by Sinopharm Chemical Reagent Co., Ltd.

[0126] n-Octyltriethoxysilane: A solvent of DBTDL manufactured by Sinopharm Chemical Reagent Co., Ltd.

[0127] Sample preparation Preparation of Silane-g-OBC pellets Silane-grafted INFUSE™ D9130.05 was prepared in a 40 mm diameter, 48 L / D12-barrel ZSK-40 Coperion twin-screw extruder. The line was equipped with a 135 kW motor with a maximum speed of 1200 revolutions per minute (RPM). INFUSE™ D9130.05 was fed to the twin-screw extruder by a loss of gravity feeder. To prevent oxidation of the polymer, nitrogen was fed to the second barrel during the compounding process to purge oxygen from the system. The melt discharge temperature was measured using a handheld thermocouple placed directly in the melt stream (barrel set temperatures from the hopper to the die were 23 / 60 / 60 / 60 / 190 / 230 / 230 / 230 / 230 / 190 / 190 / 180° C.). A mixture of silane (XIAMETER OFS-6300) and peroxide (LUPEROX101) was formed and injected into the extruder in barrel 6 via a liquid pump.

[0128] To minimize the concentration of volatile components and residual silane in the melt, a vacuum system was used to remove residual volatile components from the melt in barrel 11 of the process. A vacuum of 0.065 MPa to 0.070 MPa was used.

[0129] An underwater pelletizer equipped with a 16-hole die was used to produce the compounded pellets. Twelve of the 16 holes were plugged to inhibit the formation of pellet "chains" during spheronization. A six-blade spheronization hub was used.

[0130] The resulting OBCs had various grafted silane concentrations (0.36-2.93 wt%) based on the total weight of the silane-grafted ethylene / octene multiblock copolymer as measured using Fourier transform infrared spectroscopy (FTIR) according to Chuanmei Jiao et al., Silane Grafting and Crosslinking of Ethylene-Octene Copolymer, 41 European Polymer J. 1204 (2005), the entire contents of which are incorporated herein by reference. Table 1 lists the information of the silane-grafted resins. [Table 1] CE: Comparative Examples; IE: Examples of the Invention

[0131] Crosslinking of Silane-g-OBC pellets and foam beads Pre-crosslinking of silane-grafted OBC micropellets was carried out by two methods.

[0132] (1) The pellets are immersed in a catalyst solution of DBTDL in the solvent n-octyltriethoxysilane (DBTDL / n-octyltriethoxysilane=3 / 10) at room temperature. 0.65 wt% (based on the weight of the pellets) of this catalyst solution is placed in a sealable fluoro-plastic bottle, followed by the addition of a weighed amount of silane-grafted OBC micropellets. To ensure uniform distribution and complete immersion of the additive into the pellets, the bottle is first rolled for 1 min and then placed on a running roller (model number 88881004, Thermo Scientific) for further homogenization. After immersion, the immersed pellets are exposed to air for 7 days for wet crosslinking to ensure complete crosslinking of the silane moieties.

[0133] (2) For wet crosslinking, the silane-grafted OBC micropellets were immersed in water at 85°C for several days. The gel content was controlled by controlling the immersion time. After the desired gel content was reached, the immersion crosslinking was stopped.

[0134] Post-XL of the foam beads was carried out using method (1).

[0135] Preparation of foam beads by autoclave batch foaming The micropellets were fed into an autoclave equipped with a heating unit and a gas injection valve. The autoclave was heated to near the polymer melting temperature. At the same time, the blowing agent (in this case, high pressure CO2) was injected into the clave for saturation (0.5 h to 2 h). The pressure of the autoclave varies with the type of polymer. A typical range is 50 to 200 bar, etc. After the polymer was saturated with CO2, a rapid decompression took place and the foam beads were prepared. The prepared foam beads were usually conditioned at room temperature for several days to allow gas exchange between the inside and outside of the beads.

[0136] Performance measurement (1) Gel content Gel content was obtained in the following manner: A specimen of pellets or beads was placed in a 120 mesh metal mesh bag and boiled in 600 mL of xylene for 5 hours. The total weight of the pellets or beads in the 600 mL of xylene was approximately 2 g. After boiling for 5 hours, the mesh bag was removed and dried in a vacuum oven at 120° C. for 2 hours and then weighed. The results were recorded as a percentage (%) based on the total weight of the material. The percentage of gel generally increases with increasing crosslinking concentration.

[0137] (2) Foam density The density of the foam beads was measured using the water displacement method according to ASTM D792. The results are reported in grams per cubic centimeter (g) (g / cc or g / cm 3 ) was recorded.

[0138] (3) DMA test for evaluating energy loss characteristics -device -RSA-G2,TA equipment - Shape: Compression fixture, 15mm disc -method - Frequency Sweep -Frequency: 0.1~100rad / s -Temperature: 25℃ -Distortion: 10%

[0139] Three specimens were tested for each foam bead example and the average value at each frequency was used.

[0140] Results and Discussion (1) Foaming and bead properties Bead foam examples were prepared from silane-grafted INFUSE™ D9130.05 micropellets with various silane grafting concentrations as shown in Table 2. Crosslinking (XL) was performed before (Pre-) and after (Post-) foaming. Pre means that the silane-grafted pellets were XL by immersing in catalyst and cured at room temperature (or immersed in hot water for curing), and then the XL pellets were foamed into beads. Post means that the silane-grafted pellets were first foamed into beads, and then the resulting beads were immersed in catalyst and cured at room temperature.

[0141] Table 2 shows the foaming temperature as well as the density and gel content of the final foam beads. The foaming temperature is related to the polymer Tm, molecular weight and XL degree (i.e., gel content). If the temperature is too low, the viscosity of the polymer will be too high, resulting in too low or no expansion rate. If the temperature is too high, the melting of the crystalline phase of the polymer may cause the pellets (non-XL or low gel content) to stick together and not form free-flowing beads. However, for pellets with sufficient XL (i.e., with a relatively high gel content), a relatively high foaming temperature is required to overcome the high melt strength induced by the XL and obtain a high expansion rate. As can be seen from Table 2, a relatively high foaming temperature was required for the Pre-XL pellets compared to the non-XL pellets to achieve a similar bead density. The higher the gel content of the pellets, the higher the foaming temperature was required. This can be explained by the higher viscosity / melt strength caused by the pre-XL. For early INFUSE™ D9130.05 (CE1) pellets, it was found difficult to reach a bead density below 0.17 g / cc. In this sense, silane grafting (reduction of MI by specific chain coupling) and Pre-XL improved the foamability of the pellets. [Table 2] *85 pellets o C by immersion in water

[0142] All other XLs were performed by soaking the catalyst into the pellet or bead foam at room temperature.

[0143] DMA testing was used to characterize the tan δ (i.e., energy loss) of foam beads during compression. Lower tan δ means less energy loss and better resilience. Good resilience and low energy loss are very important in bead-filling applications.

[0144] As shown in Table 3, the same silane-grafted (1.08% grafting) pellets were made into different foam beads: CE7, non-XL, gel content 1.4%; CE8, post-XL, gel content 100%; IE9, pre-XL, gel content 95.5%. These examples had very similar foam densities. The tan δ of their DMA results at typical frequencies: 0.1, 1.0, and 10 rad / s are shown in Table 3. The tan δ curves during the frequency sweep (0.1-10 rad / s) are shown in Figure 1, but higher tan δ values ​​are available for further comparison.

[0145] Clearly, the XL (Pre- or Post-) beads had lower tan δ than the non-XL beads (CE7 and CE1), which was consistent with the common knowledge that XL can reduce the energy loss of POE foam. However, what was surprising was that the pre-XL beads (IE9) had significantly lower tan δ than the post-XL (CE8) ones (even though the post-XL ones had slightly higher gel content). IE10 used the same 1.08% silane-grafted pellets and produced a relatively dense foam bead. Still, the tan δ was significantly lower than the post-XL CE8. These results demonstrated that the pre-XL approach can significantly enhance the elasticity of the foam beads over the post-XL approach.

[0146] In CE11 and CE13, much higher silane-grafted micropellets were expanded into beads and then expanded into post-XL. The resulting gel content was 100% as well, but the crosslink density should certainly be higher than CE8 and IE9, since the catalyst DBTDL could catalyze the XL of almost all the silane in sufficient time. It is well known that higher crosslink density usually results in better elasticity. However, IE9 and IE10 still have lower tan δ than CE11 and CE13, which further demonstrated the effectiveness of the elasticity improvement by pre-XL (vs. post-XL). The foam densities of some examples were not very close. It should be noted that the foam density within the study range only had a small effect on tan δ, as shown below. [Table 3]

[0147] Although pre-XL provided an effective reduction in tan δ, the examples in Table 4 further showed that a relatively high gel content was necessary. In general, as the gel content increases, tan δ decreases. However, the change was not linear. As can be seen from CE2, CE3 and CE6, no significant reduction in tan δ was observed even with a significant increase in gel content. However, for IE9, which has a higher gel content (95.5%), a much lower tan δ was achieved. Therefore, a sufficiently high gel content is believed to be important to provide a very low tan δ, i.e., good elasticity. [Table 4]

[0148] In some of the examples above, comparisons of tan δ were made between foam beads of different densities. It is important to understand if bead density itself is a significant factor influencing tan δ and separate this from other factors (pre-XL vs. post-XL, gel content). In Table 5, three sets of examples were studied, where the silane grafting rate, XL method, and gel content were the same for the examples in each set. There was no significant difference in tan δ for the examples in each set, indicating that bead density, within the range (about 0.07-0.17 g / cc), is not the primary factor influencing tan δ. [Table 5]

[0149] (2) Morphology of foam beads Figure 2 shows the cell morphology of the foam beads. The cell sizes of these samples were comparable. All foams had a uniform cell size of less than 100 microns.

[0150] In summary, highly crosslinked polyolefin interpolymer (OBC) bead foams have much better elasticity than non-XL bead foams. Pre-XL can help to create foam beads with significantly enhanced elasticity compared to those made by the post-XL approach. The preferred gel content is ≧80%, more preferably ≧90%. Such highly crosslinked bead foams are promising for bead filling applications. The invention as originally claimed in the present application is set forth below. [1] A foam bead formed from a composition comprising one or more polyolefin interpolymers, the foam bead having a gel content of 80% or more and a tan δ at 1 rad / s of 0.11 or less. [2] The foam beads according to [1], wherein the one or more polyolefin interpolymers comprise a polyolefin elastomer. [3] The foam beads according to [1], wherein at least 70% by weight of the one or more polyolefin interpolymers are silane-grafted. [4] The foam beads of [3], wherein the silane-grafted polyolefin interpolymer has a silane grafting rate of greater than 0.3 wt.%, based on the total weight of the silane-grafted polyolefin interpolymer. [5] The foam beads of [1], wherein the foam beads are formed from the composition by crosslinking pellets of the composition prior to expanding the pellets. [6] A method for producing polyolefin foam beads, comprising: (a) providing a composition comprising one or more polyolefin interpolymers; (b) spheronizing the composition to form pellets; (c) crosslinking the pellets to a gel content of 80% or more; (d) expanding the crosslinked pellets into foam beads; The method wherein the foam beads have a tan δ at 1 rad / s of 0.11 or less. [7] The method of [6], wherein the one or more polyolefin interpolymers comprise a polyolefin elastomer, and 70 wt% or more of the one or more polyolefin interpolymers are silane-grafted. [8] The method of [7], wherein the silane-grafted polyolefin interpolymer has a silane grafting rate of greater than 0.3 wt%, based on the total weight of the silane-grafted polyolefin interpolymer. [9] The method of [6], wherein the one or more polyolefin interpolymers are selected from the group consisting of one or more ethylene / α-olefin multi-block interpolymers, one or more ethylene / α-olefin random copolymers, and any combination thereof.

[10] The method of [6], wherein the one or more polyolefin interpolymers have a melt index (MI) from 0.1 g / 10 min to 30 g / 10 min.

Claims

1. 1. A foam bead formed from a composition comprising one or more polyolefin interpolymers, the foam bead having a gel content of 80% or more and a tan delta of 0.11 or less at 1 rad / s, and 70% or more by weight of the one or more polyolefin interpolymers being silane-grafted.

2. 10. The foam bead of claim 1, wherein the one or more polyolefin interpolymers comprises a polyolefin elastomer.

3. 10. The foam bead of claim 1, wherein the silane-grafted polyolefin interpolymer has a silane grafting rate of greater than 0.3 wt%, based on the total weight of the silane-grafted polyolefin interpolymer.

4. 10. The foam bead of claim 1, wherein the foam bead is formed from the composition by crosslinking pellets of the composition prior to expanding the pellets.

5. A method for producing the foam beads according to any one of claims 1 to 4, comprising the steps of: (a) providing a composition comprising one or more polyolefin interpolymers; (b) spheronizing the composition to form pellets; (c) crosslinking the pellets to a gel content of 80% or more; (d) expanding the crosslinked pellets into foam beads; The method wherein the foam beads have a tan δ at 1 rad / s of 0.11 or less.

6. 6. The method of claim 5, wherein the silane-grafted polyolefin interpolymer has a silane grafting rate of greater than 0.3 wt%, based on the total weight of the silane-grafted polyolefin interpolymer.

7. 6. The method of claim 5, wherein the one or more polyolefin interpolymers are selected from the group consisting of one or more ethylene / α-olefin multi-block interpolymers, one or more ethylene / α-olefin random copolymers, and any combination thereof.

8. The method of claim 5, wherein the one or more polyolefin interpolymers have a melt index (MI) from 0.1 g / 10 min to 30 g / 10 min.

Citation Information

Patent Citations

  • JP1975135142A

  • Moldable thermoplastic polymer foam beads

    JP1998506935A

  • Resin molded body, and method for producing resin molded body

    JP2021100992A

  • Polymer compositions comprising crosslinkable substantially random terpolymers of ethylene, propylene, and vinyl aromatic monomers and articles fabricated therefrom.

    WO2002068530A2

  • Olefinic thermoplastic elastomer foamed particles

    WO2019009094A1